ZnO nanorods decorated with Au nanoparticles applied as gas sensors - Gasparotto, Gisane; Mazon, T.; Gasparotto, G. [UNESP]; Silva, R. A. [UNESP]; Zaghete, M. A. [UNESP]; Varela, J. A. [UNESP]; Perazolli, L. A. [UNESP] (My University, 2014)
Zinc oxide (ZnO) is an n-type semiconductor that have been considered as potential candidate for solar cells, gas sensors, photocatalysts, UV laser, field emitter, light emitting diodes (LED) application. ZnO nanostructures can be easily obtained with different morphologies by chemical and physical methods. Recently, researchers have demonstrated that the incorporation of Au nanoparticles into ZnO nanorods exhibited interesting characteristics, including bandgap emission enhancement, plasmonic effects, electric reliability reinforcement and biosensing improvement. In this paper, vertically aligned ZnO NRs were grown on Al2O3 substrate by using a simple wet chemistry method. Au NPs of 5 nm to 20 nm were deposited on ZnO NRs surface by sputtering. Sensors measures using H2 as analyte gas show a n-type semiconductor behaviour for all the samples and the sensitivity depends of gas concentration and operation temperature.
Keywords: Au nanoparticles; Gas sensors; ZnO nanorods